Systemic inflammation alters central 5-HT function as determined by pharmacological MRI. - Couch, Y; Martin, C; Howarth, C; Raley, J; Khrapitchev, A; Stratford, M; Sharp, T; Sibson, N; Anthony, D (2013)
Considerable evidence indicates a link between systemic inflammation and central 5-HT function. This study used pharmacological magnetic resonance imaging (phMRI) to study the effects of systemic inflammatory events on central 5-HT function. Changes in blood oxygenation level dependent (BOLD) contrast were detected in selected brain regions of anaesthetised rats in response to intravenous administration of the 5-HT-releasing agent, fenfluramine (10 mg/kg). Further groups of rats were pre-treated with the bacterial lipopolysaccharide (LPS; 0.5 mg/kg), to induce systemic inflammation, or the selective 5-HT2A receptor antagonist MDL100907 prior to fenfluramine. The resultant phMRI data were investigated further through measurements of cortical 5-HT release (microdialysis), and vascular responsivity, as well as a more thorough investigation of the role of the 5-HT2A receptor in sickness behaviour. Fenfluramine evoked a positive BOLD response in the motor cortex (+15.9±2%) and a negative BOLD response in the dorsal raphe nucleus (-9.9±4.2%) and nucleus accumbens (-7.7±5.3%). In all regions, BOLD responses to fenfluramine were significantly attenuated by pre-treatment with LPS (p<0.0001), but neurovascular coupling remained intact, and fenfluramine-evoked 5-HT release was not affected. However, increased expression of the 5-HT2A receptor mRNA and decreased 5-HT2A-dependent behaviour (wet-dog shakes) was a feature of the LPS treatment and may underpin the altered phMRI signal. MDL100907 (0.5 mg/kg), 5-HT2A antagonist, significantly reduced the BOLD responses to fenfluramine in all three regions (p<0.0001) in a similar manner to LPS. Together these results suggest that systemic inflammation decreases brain 5-HT activity as assessed by phMRI. However, these effects do not appear to be mediated by changes in 5-HT release, but are associated with changes in 5-HT2A-receptor-mediated downstream signalling pathways.